1995
DOI: 10.1080/09595239500185381
|View full text |Cite
|
Sign up to set email alerts
|

Harm reduction in Australia: has it worked? A review

Abstract: The literature is reviewed with a view to determining what evidence exists for the success of Australia's policy of harm minimization in relation to drug use. While there are relatively few examples of strategies which can unequivocally be said to have succeeded, there are many more for which the evidence is suggestive. While there has been a considerable mushrooming of research since the advent of the National Campaign on Drug Abuse, it would appear that little of this has measured the extent to which harm ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…According to Harwood, Hubbard, Collins, and Rachal (1998), USD4 in economic benefit can be accrued for every USD1 spent on methadone treatment. Financial benefits of the harm reduction program have been addressed by several other sources as well (Emmanuelli et al, 2006;Hawks & Lenton, 1995;Marsch, 1998;The World Bank, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to Harwood, Hubbard, Collins, and Rachal (1998), USD4 in economic benefit can be accrued for every USD1 spent on methadone treatment. Financial benefits of the harm reduction program have been addressed by several other sources as well (Emmanuelli et al, 2006;Hawks & Lenton, 1995;Marsch, 1998;The World Bank, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, an early review by Hawks & Lenton [183 summarised the changes in drug use and harms over a 10-year period in Australian history, from when harm minimisation was introduced as the national policy approach. They concluded that there is evidence for reductions in tobacco and alcohol consumption, reductions in risk behaviour among injecting drug users, low prevalence of HIV and low numbers of AIDS cases [183].…”
Section: Evaluation Of Harm Reduction As a Policy Approachmentioning
confidence: 99%
“…Research indicates that harm reduction strategies such as needle exchange and methadone maintenance are associated with reductions in: drug use [1], disease [2-4], crime [2,5] unsafe injection behaviors [1,5], drug related deaths [2], and improvements in employment and interpersonal relationships among IV drug users [5]. …”
Section: Introductionmentioning
confidence: 99%